Perlindungan Hukum Nasabah Bank Mandiri Atas Perubahan Saldo Pada Rekening Nasabah Akibat Kesalahan Sistem Teknologi Informasi - Rahmadi Indra Tektona; Fona Kartika Listiyapuji (Res Judicata, 2020)
The progress and development of technology, telecommunications, multimedia and information technology or commonly referred to as telematics can ultimately change the organizational structure, social relations, and society. Consumers can also be parties who place funds and / or utilize services available at Financial Services Institutions. Related to this, consumers who use financial services institutions include customers in banks, investors in the capital market, participants in pension funds, and others. As in the opinion of Muhamad Djumhana, the public can trust the bank if the bank has guaranteed the confidentiality of the customer's data. Every bank has an information technology system, without exception Bank Mandiri. The information technology system of each bank has a very important role. If something goes wrong even though it's a small thing it has a huge impact on the system at the bank that is running. As explained in the online media Kontan.co.id. On July 20, 2019. Related to this, customers were worried about the balance in their account, which greatly affected the customer and the customer felt disadvantaged. Related to this there is a need for legal protection for the loss-making customer, in which the customer as a consumer has the rights to the goods and / or services obtained.